Feasibility, Reliability, and Sensitivity to Change of Four Radiographic Scoring Methods in Patients With Psoriatic Arthritis. Issue 2 (February 2014) - Tillett, W.; Jadon, D.; Shaddick, G.; Robinson, G.; Sengupta, R.; Korendowych, E.; de, C. S.; McHugh, N. J.
<x xml:space="preserve">Abstract</x> Objective We set out to assess the feasibility, reliability, and sensitivity to change of 4 radiographic scoring methods in psoriatic arthritis (PsA). Methods Hand and feet radiographs from 50 patients with PsA were scored at 2 time points by 2 assessors with each of the following methods: modified Steinbrocker score, modified Sharp score (MSS), modified Sharp/van der Heijde score (SHS), and the Ratingen score for PsA. The radiographs of 10 patients were scored by both assessors to assess reliability using intraclass correlation coefficients (ICCs). Sensitivity to change was estimated using a standardized response mean (SRM) and smallest detectable change (SDC). Results The patients' mean ± SD age at baseline was 50 ± 12.1 years, the mean ± SD disease duration was 10 ± 8.4 years, and the mean ± SD followup period was 25 ± 9.6 months. Intrarater reliability was excellent for all methods (ICC >0.97). Interrater reliability was highest for the SHS (ICC 0.95–0.99). The percentage SDC for the Steinbrocker method, the Ratingen method, the MSS, and the SHS was 2.9%, 2.1%, 1.4%, and 1.2%, respectively, and the SRMs were 0.46, 0.44, 0.77, and 0.79, respectively. The mean time to score each of the Steinbrocker method, the Ratingen method, the MSS, and the SHS was 6.2, 10.5, 14.6, and 14.4 minutes, respectively. Conclusion The SHS method was the most reliable and sensitive to change but took longer to perform. The Steinbrocker method is the most feasible but lacks the sensitivity of the SHS. The SDC of the Ratingen method is close to that of the SHS and MSS, but is quicker to perform.